Modelo simple y generalizado para estimar la conductividad térmica de líquidos iónicos - Cardona-Palacio, Luis-Fernando (Revista Científica, 2021)
In this work, an empirical model is generalized to predict the thermal conductivity of ionic liquids. Initially, experimental data are collected, which include different types of anions and cations. A total of 38 ionic liquids are evaluated (28 substances for correlation and 10 substances for prediction), which corresponds to 265 experimental data. The temperature ranges vary between 273 and 390 K at atmospheric pressure (1 atm). The model is generalized using 215 experimental data, and the average deviation is around 4.72%. Then, the predictive capabilities are evaluated in 50 experimental data with an average deviation of 3.48%. The generalized model is extended to binary mixtures using a simple mixing rule with an interaction parameter, and the absolute deviation is 0.77%. Finally, the generalized model is compared with others developed in the literature, and the statistical analysis shows that it provides acceptable results.